Prevalence of pathogenic bacteria in meat products and their antimicrobial resistance pattern - Madhup, Surendra Kumar; Shrestha, Rashmi; Panta, Rakshya; Chauguthi, Laxmi; Katuwal, Nishan; Shrestha, Sunaina (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
Background: There is increase in consumption of antimicrobial agents with misuse and/or overuse of antimicrobial agents in animals and resulting to rise in antimicrobial resistance. The controlled use of antimicrobials is important for national and international policymakers to draw guidelines on its use. Assessing AMR in meat-producing industry is essential to track emerging resistant pathogens that are common between animals and humans. In this study, we have aimed to investigate the prevalence of bacteria in meat products and the antimicrobial resistance pattern in those isolates. Methods: This study is a quantitative, observational study, where we collected meat samples (n=118) from shops, in Banepa and Dhulikhel Municipality. The samples were cultured in appropriate media for isolation of bacteria. Subsequently, AMR pattern was studied through antibiotic susceptibility test using Kirby Bauer Disc Diffusion method. Results: In our study, only two sites, out of 48, did not have any pathogenic bacteria. There were total of 113 iso-lates from 118 samples. E. coli (62.8%), Enterococcus (14.1%), Klebsiella pneumoniae (11.5%), were the most prevalent bacteria in processed samples including MRSA (4%). Additionally, 81.6% of the isolated E. coli were resistant to Ampicillin and 60.5% to Ciprofloxacin and 35% to Gentamycin. 43.6% of all isolated E. coli, 100% of all Klebsiella, 100% of all Enterobacter and 25% of all Citrobacter were multi-drug resistant. The resistance was mostly observed against Ampicillin (83.3%), followed by resistance against Ciprofloxacin (64.4%), Gentamycin (58.8%), Ceftazidime (38.8%), with the lowest resistance against Sulbactam/Cefoperazone (3.3%). Conclusion: E. coli was the most prevalent organism in meat samples. Multi-drug resistance was also most common in E. coli with resistance against Ampicillin, Ciprofloxacin and Gentamycin. Therefore, we recommend for more controlled use of antibiotics in animal rearing industry and more hygienic environment at meat vendors.